Application of Steam Flooding for Heavy Oil recovery: Case Study of Suitable Nigerian Heavy Oil Reservoirs - Okoro Emmanuel Evans; Mike Onyekonwu; Joseph Ajienka (Innovations in Science and Technology Vol. 3, 2022)
Aims: Nigeria has a lot of conventional and heavy oil resources. Although majority of the conventional oil resources have been developed since independence, the heavy oil resources have remained untapped due to low primary production recovery and, as a result, concerns regarding economic sustainability under the existing fiscal framework. This chapter examines the application of Steam Flooding enhanced oil recovery (EOR) method by using suitable Nigerian heavy oil reservoirs as case study, seeks to develop a diagnostic model to predict the performance, evaluates the economics to determine the viability of the EOR method. Nigeria’s oil reserves and production will expand as heavy oil is developed. Study Design: Data was collected for two heavy oil reservoirs from two oil companies in Nigeria following a Non-disclosure Agreement (NDA) Place and Duration of Study: Emerald Energy Institute, University of Port Harcourt Nigeria, 2016 - 2021. Methodology: The screening criteria of commercially effective EOR methods were applied to select steam flooding for the studied reservoirs. Design of Experiment (DoE) was used to evaluate the reservoirs and operating parameters and to determine their optimum values, which were then used to predict the performance of the reservoirs. The economics of the steam flood technique endorsed for the reservoirs considered were also evaluated using Discounted Cash Flow Analysis (DCFA). Results: These assessments confirmed that steam flooding technique was technically and economically viable for the heavy oil reservoirs considered. The steam flood was observed to have a good recovery efficiency of 24%, as against the water flooding technique which had 13% OOIP and natural depletion of 9% for the offshore reservoir. For the onshore reservoir, the recovery efficiency was 20% for steam flood, and 4% for natural depletion. The economic analysis showed that even at a worst-case heavy oil price of US15, the project was viable. Conclusion: Steam flooding is viable, can be applied to develop heavy oil reservoirs in Nigeria that meet the screening criteria, and thus increase national oil reserve and production. Recommendation: The fiscal policy should be adjusted, especially the petroleum profit tax from 85% to 50% as an incentive to operators and investors to embark on steam flooding and other EOR methods.